Risk factors and survival analysis of patients with distant metastatic follicular thyroid cancer - Han, Na; Si, Zengmei; Wang, Guoqiang; Qin, Guohua; Lu, Chenghui; Wang, Xufu (Frontiers in Endocrinology, 2026)
ObjectiveWe aimed to identify clinicopathological risk factors associated with distant metastasis in follicular thyroid cancer (FTC) and to evaluate prognostic factors influencing survival in distant metastatic FTC patients, thereby providing evidence for risk stratification and personalized treatment strategies.MethodsIn this retrospective study, we enrolled FTC patients who underwent total thyroidectomy, subtotal thyroidectomy, or thyroid lobectomy at the Affiliated Hospital of Qingdao University from January 2014 to December 2021. Eligible patients were divided into 2 groups: the distant metastasis group (DM group) and the group with no evidence of distant metastasis during the study period (NDM group). The DM group was further divided into the survival group and the mortality group at the last follow-up.ResultsIn total, 111 patients who underwent thyroid surgery were included. 30 patients (27.03%) had distant metastasis (DM group), and 81 patients (72.97%) had no distant metastasis (NDM group). Multivariate logistic regression analysis indicated that the FTC subtype (odds ratio [OR]: 141.244; 95% confidence interval [CI]: 7.128–2798.802; P = 0.001), the number of lymph node metastases LNMs (OR: 0.028; 95% CI: 0.001–0.563; P = 0.020), T stage (OR: 0.048; 95% CI: 0.003–0.766; P = 0.032) and the type of initial surgery (OR: 175.685; 95% CI: 6.452–4783.472; P = 0.002) were independent risk factors predicting DM. Overall, the 3-year cumulative survival rates of DM patients was 83.0%. Kaplan–Meier survival analysis revealed significant differences in the 3-year survival time according to T stage (P = 0.019).ConclusionWidely invasive FTC, lymph node metastasis, T3/T4 stage, and initial total thyroidectomy are independent predictors of distant metastasis in FTC patients. For FTC patients with DM, high T stage may be related to a greater likelihood of mortality.